Human Amniotic Mesenchymal Stromal Cells Support the ex Vivo Expansion of Cord Blood Hematopoietic Stem Cells. (29th July 2021) - Orticelli, Valentina; Papait, Andrea; Vertua, Elsa; Bonassi Signoroni, Patrizia; Romele, Pietro; Di Pietro, Lorena; Magatti, Marta; Teofili, Luciana; Silini, Antonietta Rosa; Parolini, Ornella
Abstract: Currently, more than 30 000 allogeneic hematopoietic stem cell (HSC) transplantations have been performed for the treatment of hematological and nonhematological diseases using HSC from umbilical cord blood (CB). However, the wide utilization of CB as a source of HSC is limited by the low number of cells recovered. One strategy to expand ex vivo CB-HSC is represented by the use of bone marrow mesenchymal stromal cells (BM-MSCs) as a feeder to enhance HSC proliferation while maintaining HSC stemness. Indeed, BM-MSCs have been recognized as one of the most relevant players in the HSC niche. Thus, it has been hypothesized that they can support the ex vivo expansion of HSC by mimicking the physiological microenvironment present in the hematopoietic niche. Due to the role of placenta in supporting fetal hematopoiesis, MSC derived from the amniotic membrane (hAMSC) of human term placenta could represent an interesting alternative to BM-MSC as a feeder layer to enhance the proliferation and maintain HSC stemness. Therefore, in this study we investigated if hAMSC could support the ex vivo expansion of HSC and progenitor cells. The capacity of hAMSCs to support the ex vivo expansion of CB-HSC was evaluated in comparison to the control condition represented by the CB-CD34 + cells without a feeder layer. The coculture was performed at two different CD34 + :MSC ratios (1:2 and 1:8) in both cell-to-cell contact and transwell setting. After 7 days, the cells were collected and analyzed for phenotype and functionality. Our results suggest that hAMSCs represent a valuable alternative to BM-MSC to support: (a) the ex vivo expansion of CB-HSC in both contact and transwell systems, (b) the colony forming unit ability, and (c) long-term culture initiating cells ability. Overall, these findings may contribute to address the unmet need of high HSC content in CB units available for transplantation. Abstract : Ex vivo expansion of cord blood hematopoietic stem cell (HSC) and progenitor cell is required to improve efficacy of transplantation in adults. Bone marrow mesenchymal stromal cells are the gold standard for HSC expansion, but they can be difficult to obtain. Amniotic membrane-derived MSC can be a valid alternative that could help meet the demand of HSC for transplants.